(untitled) (Research, Society and Development, 2022)
Light availability and dormancy are two factors that interfere with germination and initial plant growth. This study aimed to evaluate the influence of different pre-germination treatments on the emergence and initial growth of Euterpe oleracea Mart. seedlings subjected to different levels of luminosity. A completely randomized design was adopted in a 4 × 3 factorial scheme with four methods of overcoming dormancy (intact seed, hot water at 60 °C, soaking for 24 h in water, and mechanical scarification with sandpaper No. 100) and three levels of luminosity (25 %, 65 %, and 100 %) with 16 repetitions per treatment. The emergence percentage, speed index, and mean time were analyzed. The initial growth was evaluated using the following variables: plant height, stem diameter, shoot dry mass, root dry mass, total dry mass, leaf area, and root mass ratio. There was an interaction between light factors and dormancy breakage for plant height, stem diameter, and leaf area. The variables root dry mass, shoot dry mass, and root mass ratio showed better results with full sun. It was concluded that shade treatments provided greater initial growth for the açaí palm with intact seeds.